Arterial stiffness and arterial function in adult cyanotic patients with congenital heart disease. Issue 1 (July 2017) - Trojnarska, Olga; Szczepaniak-Chicheł, Ludwina; Gabriel, Marcin; Bartczak-Rutkowska, Agnieszka; Rupa-Matysek, Joanna; Tykarski, Andrzej; Grajek, Stefan
Abstract: Background: Mortality in cyanotic patients with congenital heart diseases (CHD) is high, mainly due to cardiovascular complications. It is known that endothelial dysfunction, increased arterial stiffness, and impaired vascular function have negative influence on cardiovascular prognosis. The aim of the study was to assess parameters of arterial stiffness and vascular dysfunction in cyanotic patients with CHD as well as their potential relation to impaired blood oxygen saturation and polycythemia parameters typical for cyanosis. Methods: A total of 36 CHD cyanotic patients (17 males) (42.3 ± 16.3 years) and 35 healthy individuals (16 males) (39.6 ± 10.4 years) were enrolled. Assessed parameters were intima media thickness and flow-mediated dilatation (FMD). Assessed parameters using applanation tonometry methods were aortic systolic pressure, aortic pulse pressure (AoPP), augmentation pressure (AP), augmentation index (AI), pulse pressure amplification (PPampl), and pulse wave velocity (PWV). Results: AoPP (37.3 ± 11.1 mmHg vs. 29 ± 6.5 mmHg; p = 0.002), AP (10.1 ± 7.3 mmHg vs. 1.1 ± 3.9 mmHg; p = 0.00001), AI (24.7 ± 13.5% vs. 3.0 ± 13.6%; p = 0.00001), and PWV (7.4 ± 2.1 m/s vs. 6.3 ± 0.7 m/s; p = 0.003) were higher, and PPampl was lower (135.3 ± 16.1% vs. 160.4 ± 12.8%; p = 0.00001) in the studied group compared to controls and proved the presence of the increased stiffness of arteries. Impairment of FMD was observed (9.0 ± 5.6 vs. 10.9 ± 4.7; p = 0.04). No significant correlations were found between analyzed arterial parameters and biochemical ones characterizing cyanotic patients depicting rheological properties of blood. Conclusions: Cyanotic patients with CHD are characterized by increased arterial stiffness estimated with pulse wave analysis parameters and by deteriorated arterial function expressed with worse vasodilatative response in comparison with healthy population. It may confirm relevance of those mechanisms in development of increased rate of cardiovascular events in this population. Association between oxygen saturation or polycythemia and arterial stiffening or vascular dysfunction was not found in these patients.